Employment of Computational Analysis to Reduces Electric Energy Consumption of an Ammonia Refrigeration System at a Peak Time - de Aguiar, Danilo Barreto (Revista Interdisciplinar de Pesquisa em Engenharia, 2021)
Aspects involving the maximization of the coefficient of performance (COP) of industrial units is a topic of high importance, due to actually exists onerous tariffs of electric energy and any reduction in consumption, results in great improvements not just for the company, but also to the energetic matrix of the country, since large refrigeration units have a high electrical energy consumption. Thereby, this study has the objective of improving the COP in a refrigeration system that uses NH3 as a refrigerant fluid, through the use of mathematical modeling and computational simulation of the system in analyze. Furthermore, the electrical motors of the compressors are driven with variable speed drives (VSDs). Thus, were evaluated different conditions of regime temperature operation and values of frequency of the VSDs, with aim of obtaining the smallest electrical energy consumption, in order to meet the specific conditions of running of the installation. It was identified that the refrigeration system has some water contamination that also impacts the consumption of electrical energy. This study demonstrated that without realizing none structural modification the refrigeration system, it was possible to increase 24% the COP of the refrigeration system during the off-peak time while at peak time the percentage increase was of 63.5%. Comparing January and September months, the electrical energy save was 458438 kWh, being 80668 kWh at peak time. Moreover, comparing August and September months, the electrical energy save was of 214057 kWh, being 67983 kWh of this total consumed in peak time.